Linguistics and Philosophy: An Essay on the Philosophical Constants of Language - Gilson, Etienne, 1884-1978 (Book collections on Project MUSE., 2018)
The dual purpose of this volume-to provide a distinctively philosophical introduction to logic, as well as a logic-oriented approach to philosophy-makes it a unique and worthwhile primary text for logic or philosophy courses.